Reprezentacije spola, seksualnosti, etničnosti in družbenega razreda v sodobnih popularnih slovenskih kriminalkah - Mlačnik, Primož (Slavia Centralis, 2025)
Representations of Gender, Sexuality, Ethnicity and Social Class in Contemporary Popular Slovenian Crime Novels. The article presents a systematic deconstructive and thematic analysis of the representations of gender, sexuality, ethnicity and social class in thirty-five contemporary popular novels by Sergej Verč, Tone Frelih, Avgust Demšar, Tadej Golob, Irena Svetek and Mojca Širok. Drawing on existing studies that deal with the conservatism of the genre and the culture studies’ distinction between the conservative poetics of detective fiction and its (potentially subversive) politics of  representations, the author formulates a three-part classification of regimes of representations. The analysis shows that the Slovenian crime novels under consideration, despite some critical implications, fit into conservative and liberal regimes of representation. The dominant representations are beyond the critical regime of representations because the other representational regimes mystify class antagonisms, which rarely find themselves at the centre of crime-motivated relationships between victims, murderers and detectives.
Keywords: contemporary Slovenian crime novels; representations; gender; sexuality; ethnicity; social class